Seerah and Social Welfare: Addressing Modern Issues of Poverty, Charity, and Social Responsibility - Dr. Muhammad Shah Faisal (Al-Qanṭara, 2024)
This paper aims to discuss the function of Seerah (biography) of Prophet Muhammad (PBUH) as a model for identifying and solving contemporary issues of social welfare in the context of poverty, charity, and social justice. When comparing the Seerah with modern-day programs, such as those of the United Nations, the study shows that the Seerah offers moral, religious and pragmatic measures for creating more socialism societies. Running through the Seerah are the principles of self and community accountability, and equity, with the basics of zakat, sadaqa, and waqf. They are utilized also as means of poverty eradications and as way of establishing sound social welfare systems as proofs of the applicability of the Islamic teachings of today in addressing social injustice. The paper looks at how the Seerah provides a comprehensive model for not only the physical need for poverty alleviation but more so the emotional and spiritual aspects of social justice. It also talks about leadership of the Prophet in the formation of societies that are sensitive to the vulnerable in societies such as the poor, the orphans, and refugees. With the current global issues including climate change, mental health problems, and the refugee crisis, the Seerah issues of resilience, stewardship of the environment, and compassion are worthy lessons to learn in the twenty-first-century world. By comparing the UN frameworks to the Seerah the study shows that it’s community-based and ethical approaches can support global frameworks that rely on legal models, cooperation, and policies. The Seerah suggests ways in which people can help themselves and members of the community avoid the causes of poverty and live in more equal societies that are beneficial to more people This analysis underscores the enduring relevance of the Seerah in offering practical and spiritual guidance for tackling modern social welfare issues, while also highlighting potential synergies with contemporary global frameworks like those of the UN. Keywords: Seerah, UN, Social Welfare, Global Strategies, Spiritual Guidance, Community.